Impact of supine versus upright exercise on muscle deoxygenation heterogeneity during ramp incremental cycling is site specific - Goulding, R. P.; Okushima, D.; Fukuoka, Y.; Marwood, S.; Kondo, N.; Poole, D. C.; Barstow, T. J.; Koga, S. (European Journal of Applied Physiology, 2021)
Purpose: We tested the hypothesis that incremental ramp cycling exercise performed in the supine position (S) would be associated with an increased reliance on muscle deoxygenation (deoxy[heme]) in the deep and superficial vastus lateralis (VLd and VLs, respectively) and the superficial rectus femoris (RFs) when compared to the upright position (U). Methods: 11 healthy men completed ramp incremental exercise tests in S and U. Pulmonary V.O2 was measured breath-by-breath; deoxy[heme] was determined via time-resolved near-infrared spectroscopy in the VLd, VLs and RFs. Results: Supine exercise increased the overall change in deoxy[heme] from baseline to maximal exercise in the VLs (S: 38 ± 23 vs. U: 26 ± 15 µM, P < 0.001) and RFs (S: 36 ± 21 vs. U: 25 ± 15 µM, P < 0.001), but not in the VLd (S: 32 ± 23 vs. U: 29 ± 26 µM, P > 0.05). Conclusions: The present study supports that the impaired balance between O2 delivery and O2 utilization observed during supine exercise is a regional phenomenon within superficial muscles. Thus, deep muscle defended its O2 delivery/utilization balance against the supine-induced reductions in perfusion pressure. The differential responses of these muscle regions may be explained by a regional heterogeneity of vascular and metabolic control properties, perhaps related to fiber type composition. Introduction